Unconventional method for monitoring of waste cooking oil transesterification - Adeyemi, Nabeel A.; Mohiuddin, A. K. M.; Mirghani, Mohamed Elwathig Saeed; Jameel, Ahmed Tariq (Trans Tech Publications, Switzerland, 2012)
A technique to monitor transesterification of waste cooking oil (WCO) is presented. The technique was developed based on analogue signal from WCO, fatty acid methyl ester (FAME) and commercial palm oil (CPO). A low-pass filter design for the photodiode was used to obtain the characteristic analog signal generated by these oil samples and the signal was correlated to absorbance spectra of the oils using data from Fourier transform infrared (FTIR) equipment. A match was made between the analogue signals of the oil samples and calibrated against the FTIR spectra at 95% confidence level. Depletion of WCO during transesterification in a batch reactor correlated with the time observed for peak yield during biodiesel production. The results of the technique are discussed as a possible way to monitor transesterification process in a batch reactor.